Enhancing the quality of corn marning products through identification and optimization of the production process - Lolyka Dewi Indrasari; Ana Komari; Afiff Yudha Tripariyanto; Firman Ferdiansyah; Satrio Juwisusilo Putro (Community Empowerment, 2024)
This community service program aims to identify the production process of Marning Lancar Jaya SMEs, including raw materials, equipment used, and methods for managing raw material capacity. The methods employed include lectures, interactive discussions, and Q&A sessions with SME operators. The program successfully mapped and documented the entire production process, encompassing stages such as raw material selection, washing, boiling, drying, seasoning, and frying. Furthermore, the program enhanced the knowledge and skills of the partners in managing the production process more efficiently and systematically. By standardizing the process, the quality and competitiveness of corn marning products were significantly improved, creating potential opportunities to expand the market reach of Marning Lancar Jaya SMEs.